2005
DOI: 10.1124/jpet.105.090860
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lipophilins as Determinants of Tumor Cell Response to Estramustine

Abstract: Estramustine administered orally as estramustine phosphate (EMP) remains a major tool in hormone refractory prostate cancer chemotherapy. The presence of estramustine binding protein, prostatin, in prostate tissue may be a determinant of response to treatment. Lipophilins are secretory proteins with homology to prostatin. Reverse transcription-polymerase chain reaction was performed to estimate expression patterns of lipophilins A to C in human biopsies and cell lines resistant to estramustine. Although lipoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Figure 6C shows a simplified schematic of the entire network, which corresponds to the correlation between 363 cancer genes and 92 FDA-approved anticancer drugs. This result is consistent with previous studies, 30 estramustine has the process of inhibiting ovarian cancer tumors. Therefore, we suggest that it may be through the regulation of CREB1 pathway.…”
Section: Resultssupporting
confidence: 94%
“…Figure 6C shows a simplified schematic of the entire network, which corresponds to the correlation between 363 cancer genes and 92 FDA-approved anticancer drugs. This result is consistent with previous studies, 30 estramustine has the process of inhibiting ovarian cancer tumors. Therefore, we suggest that it may be through the regulation of CREB1 pathway.…”
Section: Resultssupporting
confidence: 94%
“…These findings are consistent with previous reports in breast cancer, suggesting that LipB mRNA overexpression correlates with favourable factors, such as retention of estrogen-receptor positivity, low-grade disease and low proliferation rate [16]. To our knowledge, few papers have investigated the functional role of LipB overexpression in cancer cells: Sjodin et al demonstrated that ectopic overexpression of lipophilin B did not affect the cell proliferation rate of breast carcinoma cells in vitro [37], while Tucker et al reported that it does not appear to mediate chemoresistance to the estradiol derivative estramustine in hormone refractory prostate cancer [38]. Despite undercharacterization of function, LipB has a well-described role as a tumor-associated antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, SCGB 2A1 (also know as mammaglobin) is predicted to be a secreted protein and when mRNA as lymph node micrometastases in breast cancer is expressed, there is an increase in the expression of mammaglobin in mammary gland of breast cancer patients, and it is also identified as a novel serum marker for detection of breast cancer (Bernstein et al 2005;Ooka et al 2000;Watson et al 1999). However, mammaglobin was found in human normal prostate tissue and absent in tumor samples without significant differences (Tucker et al 2005). Also, its mRNA levels did not vary significantly between wild-type and estramustine-resistant cells in prostate and ovarian cancer cell lines.…”
Section: Scgb 2a1mentioning
confidence: 85%